"Everyone Should Muck In": A Qualitative Study of parkrun Volunteering and Conflicting Motivations. Issue 5 (20th October 2021) - Hallett, Rachel; Gombert, Karolina; Hurley, Michael
ABSTRACT: This study looks at volunteering at parkrun, a weekly 5 k run/walk event held at almost 2, 000 different locations worldwide, which relies on volunteers. Despite large numbers of parkrunners, and an ethos encouraging occasional volunteering, some parkrunners do not volunteer which can lead to recruitment difficulties for events. Ten parkrunners were interviewed about volunteering to explore why there might be reluctance. Data were transcribed and analyzed using thematic analysis, and three interlinked themes found: becoming "hooked" on parkrun, "obligation to give back", and "reluctance to miss a run". Conflict between obligation and a desire to run or walk led to strategic volunteering to facilitate both, despite this approach potentially challenging event delivery by leaving non-run/walk roles uncovered. Findings indicate a complex and somewhat conflicting system of preference, intrapersonal and structural constraints, mutual aid, and social exchange. Gamification and the triggering of reward mechanisms may be increasing motivation to run rather than volunteer.